The United States and the European Union in the 1990s - Featherstone, Kevin. author. aut Link
XVI, 310 p.
Keywords: This text probes USA/EU relations at a critical juncture in international relations. It argues that, as both partners engage in wholesale rethinking of common interests, the marriage of convenience of the 1950s could become perilous if appropriate responses are not made to the changing world.